Pain score and quality of post cesarean section recovery with ERACS method - Ida Ruspita; Siti Cholifah; Rafhani Rosyidah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: A cesarean section must be done when regular childbirth is impossible owing to fetal or maternal health issues. One of the complications of cesarean section is pain and quality of recovery. The strategy for managing pain and quality of recovery is using the ERACS method. This method is a new technique in anesthesia with the principles of evidence-based perioperative care, a multidisciplinary approach carried out in a team, carried out on an ongoing basis, and continues to be developed.Objectives: The study aimed to use the ERACS method to calculate the pain score and the quality of recovery following cesarean section.Methods: The study was quasi-experimental with a post-test control group design. Participants in this study were mothers who had a cesarean section. The sample size in this study was 70, namely 35 treatment groups and 35 control groups. The instrument uses VAS (Visual Analog Scale) and obsQor 11Results: Statistical test for pain obtained P value = 0.000 and for quality of recovery obtained P value = 0.000Conclusions: There is a sizable distinction in pain scores carried out by the ERACS and Non ERACS methods, where the pain scores carried out by the ERACS method are lower than the non-ERACS methods, and there are differences in the quality of recovery between the ERACS and Non ERACS methods where the recovery quality scores are given by the method. ERACS is higher than non ERACS method. The ERACS method can be an alternative method to reduce postoperative morbidity. Reduction of complications through reduced use of anesthetic doses. And in the future, the development of surgical techniques has reasonable goals, such as improving public health, increasing patient comfort and peace of mind during surgery, and reducing hospitalization, which indirectly reduces costs